American Jewish Year Book 2018 The Annual Record of the North American Jewish Communities Since 1899 - Dashefsky, Arnold; Sheskin, Ira M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The American Jewish Year Book, now in its 118th year, is the annual record of the North American Jewish communities and provides insight into their major trends. The first two chapters of Part I include a special forum on "Contemporary American Jewry: Grounds for Optimism or Pessimism?" with assessments from more than 20 experts in the field. The third chapter examines antisemitism in Contemporary America. Chapters on "The Domestic Arena" and "The International Arena" analyze the year's events as they affect American Jewish communal and political affairs. Three chapters analyze the demography and geography of the US, Canada, and world Jewish populations. Part II provides lists of Jewish institutions, including federations, community centers, social service agencies, national organizations, synagogues, Hillels, day schools, camps, museums, and Israeli consulates. The final chapters present national and local Jewish periodicals and broadcast media; academic resources, including Jewish Studies programs, books, journals, articles, websites, and research libraries; and lists of major events in the past year, Jewish honorees, and obituaries. Today, as it has for over a century, the American Jewish Year Book remains the single most useful source of information and analysis on Jewish demography, social and political trends, culture, and religion. For anyone interested in Jewish life, it is simply indispensable. David Harris, CEO, American Jewish Committee (AJC), Edward and Sandra Meyer Office of the CEO The American Jewish Year Book stands as an unparalleled resource for scholars, policy makers, Jewish community professionals and thought leaders. This authoritative and comprehensive compendium of facts and figures, trends and key issues, observations and essays, is the essential guide to contemporary American Jewish life in all its dynamic multi-dimensionality. Christine Hayes, President, Association for Jewish Studies (AJS)and Robert F. and Patricia R. Weis Professor of Religious Studies in Classical Judaica at Yale University.
Chapter 1. The Quality of American Jewish Life" Steven M. Cohen and Charles S. Liebman -- Chapter 2. Forum on Contemporary American Jewry: Grounds for Optimism or Pessimism? -- Chapter 3. Anti-Semitism in Contemporary America" Tom W. Smith and Benjamin Schapiro -- Chapter 4. American Jews and the Domestic Arena (April 2017 - July 2018)" Steven Windmueller -- Chapter 5. "American Jews and the International Arena (April 2017 - July 2018)" Mitchell Bard -- Chapter 6. "United States Jewish Population, 2018" Ira M. Sheskin and Arnold Dashefsky -- Chapter 7. "Canadian Jewish Population, 2018" Charles Shahar -- Chapter 8. "World Jewish Population, 2018" Sergio DellaPergola -- Chapter 9. "Jewish Institutions: Jewish Federations; Jewish Community Centers; Jewish Human Service Agencies -- Chapter 10. "National Jewish Organization" Ira M. Sheskin, Arnold Dashefsky, and Sarah Markowitz -- Chapter 11. "Jewish Museums and Holocaust Museums, Memorials, and Monuments" Ira M. Sheskin, Arnold Dashefsky, and Sarah Markowitz -- Chapter 12. "Jewish Press: National Jewish Periodicals and Broadcast Media; Local Jewish Periodicals" -- Chapter 13. Academic Resources: Programs in Jewish Studies, Holocaust and Genocide Studies, Israel Studies, Professorships of Israel Studies, and Jewish Social Work; Major Books on the North American Jewish Communities; Academic Journals in or about the North American Jewish Communities; Scholarly Articles on the Study of the North American Jewish Communities; Websites and Organizations for Research on North American Jewish Communities; Major Judaic Research and Holocaust Research Libraries -- Chapter 14. "Transitions: Major Events, Honorees, and Obituaries".
Keywords: Race; Judaism; Human geography; Race and Ethnicity Studies; Judaism; Human Geography